2021
DOI: 10.1038/s41598-021-99911-8
|View full text |Cite
|
Sign up to set email alerts
|

Dried blood sample analysis by antibody array across the total testing process

Abstract: Dried blood samples (DBSs) have many advantages; yet, impediments have limited the clinical utilization of DBSs. We developed a novel volumetric sampling device that collects a precise volume of blood, which overcomes the heterogeneity and hematocrit issues commonly encountered in a traditional DBS card collection as well as allowing for more efficient extraction and processing procedures and thus, more efficient quantitation, by using the entire sample. We also provided a thorough procedure validation using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…We performed a one-way ANOVA to compare the effect of five different hematocrit values on the quantitation of transferrin receptor protein from pDPS cards, which revealed that there was not a statistically significant difference between mean transferrin receptor protein concentrations for whole blood samples with varying hematocrit values ( F = [1.893] and p = 0.15). The overall yield of analytes eluted from TFN can be improved by introducing low concentrations of surfactants into the elution buffer to encourage the resolubilization of proteins following the drying step (vide infra) . However, maintaining a consistent concentration of this soluble analyte provided confidence in the volume metering capabilities of this device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a one-way ANOVA to compare the effect of five different hematocrit values on the quantitation of transferrin receptor protein from pDPS cards, which revealed that there was not a statistically significant difference between mean transferrin receptor protein concentrations for whole blood samples with varying hematocrit values ( F = [1.893] and p = 0.15). The overall yield of analytes eluted from TFN can be improved by introducing low concentrations of surfactants into the elution buffer to encourage the resolubilization of proteins following the drying step (vide infra) . However, maintaining a consistent concentration of this soluble analyte provided confidence in the volume metering capabilities of this device.…”
Section: Resultsmentioning
confidence: 99%
“…The overall yield of analytes eluted from TFN can be improved by introducing low concentrations of surfactants into the elution buffer to encourage the resolubilization of proteins following the drying step (vide infra). 44 However, maintaining a consistent concentration of this soluble analyte provided confidence in the volume metering capabilities of this device. Additionally, reproducibly producing a discrete volume of liquid plasma� independent of the hematocrit�can enable quantitative analysis to aid in a clinical diagnosis rather than simply detecting the presence of an analyte.…”
Section: ■ Results and Discussion Pdps Cards Reproducibly Fill Indepe...mentioning
confidence: 99%
“…The overall yield of analyte eluted from TFN can be improved by introducing low concentrations of surfactants into the elution buffer to encourage the re-solubilization of proteins following the drying step (vide infra). 43 However, maintaining a consistent concentration of this soluble analyte provided confidence in the volume metering capabilities of this device. Additionally, reproducibly producing a discrete volume of liquid plasma-independently of the hematocrit-can enable quantitative analysis to aid in a clinical diagnosis rather than simply detecting the presence of an analyte.…”
Section: Pdps Cards Reproducibly Fill Independently Of Hematocrit Valuementioning
confidence: 99%
“… 25 , 26 Despite a number of issues related to DBS sampling, such as the impact of hematocrit on accurate quantification, 27 , 28 devices for accurate volumetric collection 29 have proven to overcome most issues associated with conventional DBS collection. 30 32 …”
Section: Introductionmentioning
confidence: 99%
“…Dried blood spot (DBS) sampling is a patient-centric sampling method, used to collect, ship, and store blood, that has the potential to alleviate some of the problems associated with the preanalytical phase. However, the capability to accurately quantify low-abundant biomarkers relies on the quality of the dried sample, the ability to quantify from it (through volume or intrinsic markers in the sample), the efficiency of recovery upon elution, and the sensitivity of the assay downstream since the elution procedure may lead to a dilution of 5–10 times or even more. , Despite a number of issues related to DBS sampling, such as the impact of hematocrit on accurate quantification, , devices for accurate volumetric collection have proven to overcome most issues associated with conventional DBS collection. …”
Section: Introductionmentioning
confidence: 99%